Prinsip Keadilan Dalam Penyelesaian Sengketa Hutang Piutang Di Masyarakat Sampang Madura Melalui Gadai Tanah - Purwanto Dwi S (HKI IAI Miftahul Ulum Pamekasan, 2022)
The Basic Agrarian Law does not only draw from the values of religious law but also draws from the values of customary law, as stated in Article 5 of Law no. 5 of 1960 concerning Basic Agrarian Regulations. This article aims to find out the principles of justice in settlement of debt and credit disputes in the Sampang Madura community through land pawning. Through qualitative research methods with a case study approach, the best solution to debt and credit disputes can be resolved wisely by staying true to legal law while accommodating local policies. Thus the implications of the findings in this article serve as a guide for similar cases, although specifically the principles of justice found are assumed to apply or be effective in areas that have a similar culture.